Structural and developmental characteristics of Japanese elite athletes: a longitudinal case study of a talent identification and development programme in Fukuoka prefecture - Hagiwara, M.; Kinugasa, T.; Haramura, M.; Nakao, T.; Teshima, K.; Yamashita, S.; Shirai, K. (Frontiers in Sports and Active Living, 2026)
Purpose: This study longitudinally examined the influence of sporting history, the relative age effect (RAE), and physical development on the elite progression of Japanese athletes from a local talent identification and development (L-TID) programme to senior elite status.